Stator earth fault detection & evaluation of delaminated stator bar ground wall-insulation of generator G-4 of HPP Chhukha – A case study - Wangdi, Rinchen; Sharma, Deepen; Dorji, Tshewang; Chophel, Tenzin; Tobgay, Ugyen (Bhutan Journal of Research and Development, 2022)
Protective devices are employed to monitor and isolate the faulty equipment whenever faults occur in the power system. In the generator protection system, a conventional stator earth fault protection, which is based on residual over voltage (aka neutral voltage displacement) principle, is observed to be inadequate. The paper thus, discusses on how helpful a modern approach of 100% stator earth fault protection scheme is, and proven effective in generator G- 4 of Chhukha Hydropower Plant (CHP). Also, to assess the health of stator windings, insulation resistance (IR) measurement is the foremost test that needs to be performed to qualify for go- ahead with other insulation tests. HV DC ramp and tan ẟ tests are not uncommon as the tests have been proven useful in evaluating the condition of the groundwall insulation of stator coils. Therefore, this paper also illustrates on investigation and analysis of the test results obtained for a bar, suspected to have groundwall insulation breakdown, due to a number of factors. The test results obtained are compared with that of the other test specimens.